Women principals in Cyprus primary schools: barriers to accession - Karamanidou, Maria (2017)
This thesis focuses on the barriers that women principals face in Cypriot primary schools. This research had six aims including the overarching aim. The overarching aim of this research is to examine the career progress of female principals in Cyprus primary schools and to address the apparent under-representation of women in leadership positions. The research also aimed to establish the barriers that female leaders face in order to be promoted as principals, and how they can be overcome. Another aim was to establish how gender issues play a part in creating barriers to promotion as a school principal and how these may subsequently affect them in leading the school. A third consideration was to comprehend what barriers women may have faced in their childhood years and to establish whether, and to what extent, female leaders face internal and external barriers in Cyprus schools. The research also sought to identify the support or enablers that may facilitate women’s career progression.